2010
DOI: 10.1002/rra.1453
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and assessment of a river restoration project in central New York

Abstract: A widespread lack of post‐project appraisals (PPAs) not only hinders progress in the field of river restoration but also limits the application of adaptive management – a powerful heuristic tool particularly well suited to dynamic fluvial environments. In an effort to contribute to the limited body of scientific literature pertaining to PPAs, we evaluated a stream restoration project completed in the fall of 2005 in central New York. Using a variety of evaluation approaches, we documented both successes (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…Although aerial images are not as accurate as other methods, aerial photography is the only method that can be used to measure historical streambank retreat. Buchanan et al [13], Pracheil [20], Mittelstet et al [26], Heeren et al [27], and Purvis and Fox [28] successfully analyzed aerial photography analysis to quantify the streambank erosion.…”
Section: Lateral Streambank Erosionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although aerial images are not as accurate as other methods, aerial photography is the only method that can be used to measure historical streambank retreat. Buchanan et al [13], Pracheil [20], Mittelstet et al [26], Heeren et al [27], and Purvis and Fox [28] successfully analyzed aerial photography analysis to quantify the streambank erosion.…”
Section: Lateral Streambank Erosionmentioning
confidence: 99%
“…He also found that riprap (similar to the rock toe and gravel bank) fully protected the streambanks. Two years after installation, Buchanan et al [13] found that 28% of the bank vanes (which are vanes that do not go across the entire river width but protect only the bank at the desired location) failed and that 36% were impaired. One limitation to comparing differences in streambank erosion rates among the practices observed within the present study is the limited number of observations for several of the practices.…”
Section: Prestabilization and Poststabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Each structure was 1 m long (thick) in the direction of flow, 3 m long perpendicular to the flow, and each extended 0.3 m above the streambed and approximately 0.2 m (one computational layer) into the streambed (Azinheira et al, 2014). These structures were spaced 45 m apart consistent with restoration guidance and prior research for a stream of this discharge (Rosgen, 2001;Crispell and Endreny, 2009;Buchanan et al, 2012;Azinheira et al, 2014).…”
Section: Hydraulic Parameters and Boundary Conditionsmentioning
confidence: 87%